False-positive galactomannan antigen testing in pulmonary nocardiosis. (17th September 2020) - Haran, Arnon; Temper, Violeta; Assous, Marc; Bergel, Michael; Chahanian, Noga; Elinav, Hila; Korem, Maya
Abstract: Early diagnosis of invasive aspergillosis (IA) is facilitated by detection of galactomannan (GM) in serum and bronchoalveolar lavage fluid (BALF) using an enzyme-linked immunosorbent assay (ELISA). Although accurate, false positive results have been reported with these tests in numerous contexts. We report for the first time the occurrence of false positive GM ELISA due to nocardiosis, initially in a clinical sample of BALF from a patient with pulmonary nocardiosis, and subsequently corroborated by in vitro reactivity of 26% of tested isolates. Since patients at risk for IA are also at risk for nocardiosis, this finding has important clinical implications. Lay Summary: Early diagnosis of aspergillosis has been facilitated by the routine use of antibody-based detection of galactomannan in various bodily fluids. We report for the first time the occurrence of false positive results of this assay in the context of nocardiosis.